Surface plasmon–catalyzed oxidation of 4-aminodiphenyl disulfide for determination of Ag+ ion in aqueous samples - Sun, Ye; Zhang, Yao; Wang, Yue; Xia, Lixin (Mikrochimica acta (1966), 2020)
A new sensor for determination of Ag + ion (Ag + ) by surface-enhanced Raman scattering (SERS) is reported. Gold nanoparticles (AuNPs) and 4-aminodiphenyl disulfide (APDS) were chosen as the SERS substrate and probe molecule, respectively. With the addition of Ag + , three new peaks (1141, 1392, and 1435 cm −1 ) appeared in the SERS spectrum, indicating that the conversion of APDS to p , p ′-dimercaptoazobenzene (DMAB) was achieved. As the concentration of Ag + increased, the conversion of APDS to DMAB also increased and showed a good linear relationship ( R 2 = 0.9746) in the range of 10 to 100 μM of Ag + . The limit of detection (LOD) was 7 μM. Compared with the traditional determination method, the SERS method is convenient and fast and requires no complicated preprocessing. Graphical abstract